Inflammation May Alter the Association Between Serum and Milk Fatty Acid Profiles in Women With Low Milk Production. (14th June 2022) - Walker, Rachel; Nommsen-Rivers, Laurie; Harvatine, Kevin; Riddle, Sarah; Ross, A Catharine; Wagner, Erin; Gernand, Alison
Abstract: Objectives: Women with insufficient milk production are more likely to have obesity linked with chronic inflammation. The inflammatory cytokine tumor necrosis factor α (TNF-α) inhibits lipoprotein lipase-mediated fatty acid uptake. We hypothesized that serum fatty acid profiles would be positively related with milk fatty acids in normal lactation, but the relation would be modified in mothers with low milk production and inflammation. Methods: In this ancillary analysis of a low milk supply trial, milk production was measured in mothers 2–8 weeks postpartum and categorized into 3 groups as very low (LOW; < 300 mL/d; n = 23), moderately low/normal (MODERATE; >300 mL/d; n = 20), or exclusively breastfeeding controls with adequate production (ADEQUATE; >700 mL/d; n = 18). Milk and fasting serum fatty acids were methylated and analyzed by gas chromatography. Milk TNF-α was measured by ultra-sensitive ELISA, and stratified as detected or undetected. Associations between serum and milk fatty acids were assessed by linear regression, with milk production group included in the model. Results: LOW mothers were more likely to have obesity (P < 0.01) and detectable milk TNF-α (p = 0.04) compared to MODERATE and ADEQUATE mothers (mean BMI (SD): 37.2(9.6), 29.0(5.3), 26.1(6.0); TNF-α: 67%, 32%, 33%, respectively). The relation between serum and milk fatty acids was modified by group for saturated fatty acids (SFA; pint  < 0.01), monounsaturated fatty acids (MUFA; pint  = 0.02), and polyunsaturated fatty acids (PUFA; pint  < 0.01). Serum SFA positively predicted milk SFA in ADEQUATE mothers (r = 0.75, P < 0.01), but the association was not significant in LOW or MODERATE mothers. Similarly, serum PUFA positively predicted milk PUFA in ADEQUATE (r = 0.81, P < 0.01) but not LOW or MODERATE mothers. Only MODERATE mothers had a significant positive association between serum and milk MUFA (r = 0.59, P < 0.01), with no significant association in LOW or ADEQUATE groups. Conclusions: Mothers with low milk production were more likely to have obesity and detectable milk TNF-α and did not exhibit a relation between serum and milk fatty acids, but serum SFA and PUFA were strongly positively associated with milk fatty acids in exclusive breastfeeding. These data support the hypothesis that inflammation suppresses lipoprotein lipase activity, reducing mammary gland fatty acid uptake. Funding Sources: NIH and USDA.